The Characterization of Wastewater at the Pesanggaran Slaughterhouse - Suardana, I Wayan (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
This research aimed to analyze the ability of wastewater treatment to reduce the pollutant component at the wastewater that produced by slaughtered activities, so that the hazards that impacted by the activities to the community that lived surrounding the area can be monitoring. This experiment used Randomize Completely Block Design, with 5 point collected samples as block and 5 times repeatly as treatment. Result of the research at 50 meters from the end of wastewater treatment to generally sewage for the temperature parameter (26.40 + 0.42 0C), pH (6.97 + 0.11), BOD5 (124.200 + 8.352 mg/l) and COD (255.000 + 20.07 mg/l) indicated equal with the standard. The result means the wastewater management at Pesanggaran slaughterhouse is effective to produce wastewater quality with the second standard (waste water standard for agriculture) of wastewater quality according to the Indonesian National Standard. (Animal Production 9(2): 116-122 (2007)Â Key Words : Slaughterhouse, temperature, pH, BOD5, COD